Ethiopian Manuscripts in the State and Private Collections of St Petersburg: An Overview - Gusarova, Ekaterina (Aethiopica, 2015)
For more than two centuries St Petersburg, the capital of the former Russian Empire, has been famous for its collections of Ethiopian manuscripts, objects of art and documents concerning Ethiopian history. They are concentrated in three state institutions and in several private collections of African art. This article provides a short history of formation of Ethiopian manuscript collections of Russia and describes the process of their description and study. Some interesting and unpublished items were generally described and their miniatures published.